2017
DOI: 10.1136/bjophthalmol-2016-309852
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc haemorrhages at baseline as a risk factor for poor outcome in the Idiopathic Intracranial Hypertension Treatment Trial

Abstract: NCT01003639, Post-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
12
1
2
Order By: Relevance
“…Our study supports the finding in that Frisén grade at presentation was associated with worse final VA and also adds an additional poor prognostic factor of severe CWS at presentation. It was suggested that ODH may be a marker of poor visual prognosis by the IIHTT, 11 but this was not found to be the case in our previous study of adults 9 and in this cohort of pediatric IIH patients when controlling for the severity of papilledema. In the IIHTT, ODH as a predictor of worse visual outcome was not assessed independent of Frisén grade, which is likely the reason for the differences in our studies.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Our study supports the finding in that Frisén grade at presentation was associated with worse final VA and also adds an additional poor prognostic factor of severe CWS at presentation. It was suggested that ODH may be a marker of poor visual prognosis by the IIHTT, 11 but this was not found to be the case in our previous study of adults 9 and in this cohort of pediatric IIH patients when controlling for the severity of papilledema. In the IIHTT, ODH as a predictor of worse visual outcome was not assessed independent of Frisén grade, which is likely the reason for the differences in our studies.…”
Section: Discussioncontrasting
confidence: 77%
“…[8][9][10] The Idiopathic Intracranial Hypertension Treatment Trial (IIHTT) proposed that optic disc hemorrhages (ODH) may be a risk factor for poor visual outcome in adults since this was a more frequent finding in the treatment failure group. 11 We performed a study of 708 eyes of 360 adult IIH patients and found that ODH and peripapillary cotton wool spots (CWS) were not an independent risk factor for a poor visual outcome in IIH when controlling for the severity of the papilledema. 9 The goal of this study was to determine whether optic nerve appearance, particularly ODH and CWS, were an independent risk factor for visual outcome in pediatric IIH.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent visual loss is the most feared complication of this disease. Risk factors associated with irreversible visual loss include recent weight gain, papilledema severity, optic disc hemorrhages, decreased visual acuity and visual field loss at the time of presentation, early optic nerve atrophy, and hypertension. Symptom duration, transient visual obscurations, pulsatile tinnitus, headache severity, and the actual number of the OP have not been shown to influence long‐term prognosis.…”
Section: Secondary Causesmentioning
confidence: 99%
“…For example, the severity of the papilledema and loss of visual acuity correlate with the incidence of therapy failure [35]. The same is true for evidence of hemorrhages in the area of the papilla, which can already be present with mild visual impairment [36].…”
Section: Visual Disordersmentioning
confidence: 97%